Hubungan Social Comparison dengan Dietary Behavior pada Mahasiswa Keperawatan Universitas Pendidikan Indonesia Kampus Sumedang - Bahari, Rosyidah Rizki; Setiadi, Diding Kelana; Astuti, Ayu Prameswari Kusuma (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Social comparison is a social phenomenon in individuals with a tendency to compare themselves to others, especially in terms of physique. Social comparison is a factor influencing individuals to internalize the thin body shapes seen on social media, leading them to engage in dietary behaviors. This study aims to determine the relationship between social comparison and dietary behavior in nursing students. As for the method of this research, it uses a descriptive quantitative approach with a correlational method. The sample was determined using the cluster random sampling method, with a sample size of 215 students. The measuring instruments used for the research were the Social Comparison Instrument, adapted from The Upward and Downward Appearance Comparison Scale (UDACS) to measure social comparison, and the Dutch Eating Behavior Questionnaire (DEBQ) to measure dietary behavior. The results obtained thru analysis and Pearson product-moment correlation test are P value = 0.003 and R value (Pearson's r) = 0.200. There is a significant positive relationship between social comparison and dietary behavior, but it is weak. The more an individual engages in social comparison, the more likely they are to engage in dietary behaviors. This research is expected to enable nursing students at the Sumedang Campus of the Indonesian Education University) to manage social comparison and dietary behavior. Students can apply self-control and self-acceptance. .